2015
DOI: 10.1210/en.2015-1265
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Glucocorticoid Feedback Inhibition of ACTH Secretion Involves Ligand-Dependent Membrane Association of Glucocorticoid Receptors

Abstract: The hypothesis that rapid glucocorticoid inhibition of pituitary ACTH secretion mediates a feedforward/feedback mechanism responsible for the hourly glucocorticoid pulsatility was tested in cultured pituitary cells. Perifusion with 30 pM CRH caused sustained the elevation of ACTH secretion. Superimposed corticosterone pulses inhibited CRH-stimulated ACTH release, depending on prior glucocorticoid clearance. When CRH perifusion started after 2 hours of glucocorticoid-free medium, corticosterone levels in the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
57
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 71 publications
(65 citation statements)
references
References 62 publications
4
57
4
Order By: Relevance
“…Preliminary experiments in a previous study indicated that 5-minuteincreasing pulses of CRH resulted in concentration-dependent ACTH secretion with a threshold of 30 pM [20]. In this study, the lowest physiological levels of CRH, 10pM was not able to produce a marked increase in ACTH secretion (Fig.…”
Section: Discussionmentioning
confidence: 49%
“…Preliminary experiments in a previous study indicated that 5-minuteincreasing pulses of CRH resulted in concentration-dependent ACTH secretion with a threshold of 30 pM [20]. In this study, the lowest physiological levels of CRH, 10pM was not able to produce a marked increase in ACTH secretion (Fig.…”
Section: Discussionmentioning
confidence: 49%
“…After cells were harvested, cytoplasmic, membrane, and nuclear protein fractions were separated using the subcellular protein fractionation kit for cultured cells (Pierce, Life Technologies) as previously described [22]. Protein concentrations were determined by the bicinchoninic acid protein assay.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, mifepristone is inconsistent in elevating LH levels when administered to healthy women during the early follicular phase [112][113][114] and fails to reverse exogenous E 2 and progesterone-induced slowing of GnRH pulse frequency in healthy women when it replaces 10 days of prior exogenous progesterone therapy [69]. Such unexpectedly mixed effects of mifepristone may stem from its suppression of Ca ++ -mediated membrane depolarization [115] crucial for exocytosis of GnRH and LH, and from its antagonism at the glucocorticoid receptor [116], potentially inducing compensatory elevation in hypothalamic CRH, and potentially, GnRH suppression [117].…”
Section: Discussionmentioning
confidence: 99%